The effect of reaction training vs sprints training on speed and power - Sharin, M.; Zanelli, A.; Wygand, J.; Otto, R. M. (Medicine & Science in Sports & Exercise, 1997)
Female soccer players (N = 23) participated in either reaction coach, sprint training, or control programs. The control program did not engage in any extra training. The reaction coach group used a device to provide sound and light cues for explosive movements. Both forms of training produced improved performances over the control group. There was no difference between either forms of training indicating that traditional sprint training was just as effective as was a form of training that required specialized equipment and conduct. Implication. Traditional sprint training is as effective as specialized device-dependent training designed to increase reaction and movement time.